1999
DOI: 10.1080/01616412.1999.11741017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of craniopharyngioma fluid on femoral vessels of rat

Abstract: Craniopharyngioma fluid spillage during surgery is reported to cause aseptic meningitis, but effects of the spillage on vessels have not yet been studied. Therefore we experimentally studied the effect of external contact on femoral vessels of the rat to assess its possible role in the cerebral vascular complications. The major direct effect of the craniopharyngioma fluid on the femoral vessels was vasospasm, appearing on the fourth day after instillation. The vasospasm was observed in 83% of femoral vessels s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…An experimental model with rat femoral arteries has demonstrated that direct contact of the vessel with craniopharyngioma cystic fluid induces arterial vasospasm. 13 Therefore, the craniopharyngioma cyst must be entered in a controlled fashion. A small opening is created in the cyst wall with simultaneous aspiration at the puncture site to avoid spillage of cyst contents into the subarachnoid space.…”
Section: Learning Curve In Craniopharyngioma Surgerymentioning
confidence: 99%
“…An experimental model with rat femoral arteries has demonstrated that direct contact of the vessel with craniopharyngioma cystic fluid induces arterial vasospasm. 13 Therefore, the craniopharyngioma cyst must be entered in a controlled fashion. A small opening is created in the cyst wall with simultaneous aspiration at the puncture site to avoid spillage of cyst contents into the subarachnoid space.…”
Section: Learning Curve In Craniopharyngioma Surgerymentioning
confidence: 99%
“…However, a delayed vasospasm induced by chemical effect of the cystic components cannot be entirely excluded [1,4].…”
Section: Discussionmentioning
confidence: 98%
“…Vasospasm following removal of craniopharyngioma has only been described in a few instances [2,3] and has been attributed to chemical effects of fluid from cystic craniopharyngioma [1,4]. Shida et al report a spontaneous rupture of a craniopharyngioma cyst that may have caused symptomatic vasospasm of major cranial vessels before surgical treatment or cranial irradiation.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations